1947
DOI: 10.1001/archneurpsyc.1947.02300240074003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Motion Sickness

Abstract: SEASICKNESS is a serious inconvenience to many people in times of peace. In times of war, however, motion sickness in its various forms may be a very real threat to the success of operations in the air and on the sea. Army personnel are apt to be affected in very large numbers, when airborne or in landing craft, since they have little opportunity to become acclimatized, as does the sailor or the airman.The literature on motion sickness up to 1942 has been reviewed elsewhere.1 Since that time a large amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1951
1951
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…VIMS can even be stronger than MS caused by actual rotation because visually induced stimulation of canal projection areas in the brain never ceases, unlike an actual sustained rotation in which the canal output declines after the initial acceleration with a time constant of 10-15 s. Numerous studies have shown that MS susceptibility in various situations is positively correlated with the duration and magnitude of canal-ocular reflexes, 52,62,87 although other studies have shown no relationship. 13,60,68 No study to date has shown a negative relationship between the strength of canal outputs and MS susceptibility, however.…”
Section: Intravestibular Imbalance and Motion Sicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…VIMS can even be stronger than MS caused by actual rotation because visually induced stimulation of canal projection areas in the brain never ceases, unlike an actual sustained rotation in which the canal output declines after the initial acceleration with a time constant of 10-15 s. Numerous studies have shown that MS susceptibility in various situations is positively correlated with the duration and magnitude of canal-ocular reflexes, 52,62,87 although other studies have shown no relationship. 13,60,68 No study to date has shown a negative relationship between the strength of canal outputs and MS susceptibility, however.…”
Section: Intravestibular Imbalance and Motion Sicknessmentioning
confidence: 99%
“…Nor is increased loading of the otoliths provocative, as moving from a microgravity to a 1-G environment does not generate substantial MS, despite a wide variety of sensory conflicts. 92 Indeed, anecdotal reports suggest the return to a 1-G environment following spaceflight may confer later immunity to terrestrial MS. 92 The beneficial effects of normal graviception is further illustrated by the fact that roll oscillation is not very provocative in the erect position, 46,68 when otolith shearing would be present, but is highly provocative when supine, 43 when otolith graviceptor signals do not accompany the movement of the head.…”
Section: Intravestibular Imbalance and Motion Sicknessmentioning
confidence: 99%
“…For as long as people have been exposed to motion, the occurrence of motion sickness has affected personal well being (Morton, Cipriani, & McEachern, 1947). However, perceiving motion sickness does not require exposure to actual motion.…”
Section: Introductionmentioning
confidence: 99%
“…Canadian wartime investigators made some of the most significant contributions toward motion sickness prevention and understanding. The "roll-pitch rocker" was used in these studies to simulate vehicle motion (Morton et al, 1947). Later, the two-and four-pole swings became the primary research tools (Manning, 1943;Manning & Stewart, 1949).…”
Section: Motion Sickness Susceptibility Factorsmentioning
confidence: 99%